The View of Samin People on The Moral Dilemma of Wayang Story - Mikka Wildha Nurrochsyam (Antropologi Indonesia, 2021)
Followers of Saminism, known as Sedulur Sikep, were fond of watching wayang performance. However, wayang performance had many war scenes that contradict the Samin’s moral teaching of non-violence. This study seeks to answer the question rose from the apparent contradiction—how do the Samin people address the moral dilemma presented in wayang performance based on their own moral teachings? This study has three objectives: describing the wayang performance of the Samin community; analyzing the moral view of Samin people based on the scenes of moral dilemmas in wayang performance; and, proposing a strategy to develop wayang performance that is suitable to Samin people and their moral teachings. The research was conducted with a qualitative approach, using in-depth interviews with Samin leaders and figures as the method of data collection. The data analysis was carried out using Lawrence Kohlberg's theory of moral development. The results showed that the moral views of Samin people tend to be staged in the conventional level of Kohlberg’s scheme in which the group morality is dominant. Moreover, their moral considerations can be placed in the third and fourth stage of moral development, namely ‘the orientation of interpersonal agreement’ and ‘the orientation of law and order,’ respectively. As for the development of wayang performance for Samin people, this article suggests that it can be done by elaborating aesthetic and ethical creativity on the pakeliran based on the teachings of Saminism.